Landscape‐scale patterns of nutrient enrichment in a coral reef ecosystem: implications for coral to algae phase shifts. Issue 1 (21st October 2020) - Adam, Thomas C.; Burkepile, Deron E.; Holbrook, Sally J.; Carpenter, Robert C.; Claudet, Joachim; Loiseau, Charles; Thiault, Lauric; Brooks, Andrew J.; Washburn, Libe; Schmitt, Russell J.
Abstract: Nutrient pollution is altering coastal ecosystems worldwide. On coral reefs, excess nutrients can favor the production of algae at the expense of reef‐building corals, yet the role of nutrients in driving community changes such as shifts from coral to macroalgae is not well understood. Here we investigate the potential role of anthropogenic nutrient loading in driving recent coral‐to‐macroalgae phase shifts on reefs in the lagoons surrounding the Pacific island of Moorea, French Polynesia. We use nitrogen (N) tissue content and stable isotopes (δ 15 N) in an abundant macroalga ( Turbinaria ornata ) together with empirical models of nutrient discharge to describe spatial and temporal patterns of nutrient enrichment in the lagoons. We then employ time series data to test whether recent increases in macroalgae are associated with nutrients. Our results revealed that patterns of N enrichment were linked to several factors, including rainfall, wave‐driven circulation, and distance from anthropogenic nutrient sources, especially human sewage. Reefs near large watersheds, where inputs of N from sewage and agriculture are high, have been consistently enriched in N for at least the last decade. In many of these areas, corals have decreased and macroalgae have increased, while reefs with lower levels of N input have maintained high cover of coral and low cover of macroalgae. Importantly, these patchy phase shifts to macroalgae have occurred despite substantial island‐wide increases in the density and biomass of herbivorous fishes over the time period. Together, these results indicate that nutrient loading may be an important driver of coral‐to‐macroalgae phase shifts in the lagoons of Moorea even though the reefs harbor an abundant and diverse herbivore assemblage. These results emphasize the important role that bottom‐up factors can play in driving coral‐to‐macroalgae phase shifts and underscore the critical importance of watershed management for reducing inputs of nutrients and other land‐based pollutants to coral reef ecosystems.